2014
DOI: 10.21566/tbmaed.14229
|View full text |Cite
|
Sign up to set email alerts
|

Ekmeklik Buğdayda (Triticum aestivum L.) Tane Verimi ile Bazı Tarımsal Karakterler Arası İlişkiler

Abstract: yıllarında Edirne'de yürütülmüştür. Deneme 22 çeşit ile tesadüf blokları deneme desenine göre 4 tekrarlamalı olarak kurulmuştur. Tane verimi, bayrak yaprak alanı, bitki örtüsü sıcaklığı, bayrak yaprak klorofil miktarı, yaprak su tutma kapasitesi, kuru madde oranı, bitki boyu, başaklanma ve olgunlaşma gün sayıları gibi özellikler incelenmiştir. AbstractThis study was carried out to determine grain yield, some agricultural and physiological characteristics of the some bread wheat varieties in 2009-2010 and 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Even in the same varieties planted in different places and years, significant differences occur due to regional and climatic differences [36][37]. According to the average table (Table 5), the highest canopy temperature was obtained from the PLS x KLC hybrid with 31.67 o C, while the lowest vegetation (canopy) temperature was obtained from the Ince-04 variety with 29.59 o C. Studies show that the canopy temperature is inversely proportional to the SPAD value [38]. In our study, this inverse ratio was revealed (Table 5).…”
Section: Canopy Temperaturementioning
confidence: 99%
“…Even in the same varieties planted in different places and years, significant differences occur due to regional and climatic differences [36][37]. According to the average table (Table 5), the highest canopy temperature was obtained from the PLS x KLC hybrid with 31.67 o C, while the lowest vegetation (canopy) temperature was obtained from the Ince-04 variety with 29.59 o C. Studies show that the canopy temperature is inversely proportional to the SPAD value [38]. In our study, this inverse ratio was revealed (Table 5).…”
Section: Canopy Temperaturementioning
confidence: 99%